Topiramate mitigates 3-nitropropionic acid-induced striatal neurotoxicity via modulation of AMPA receptors. (August 2018) - Shalaby, Heba N.; El-Tanbouly, Dalia M.; Zaki, Hala F.
Abstract: Prevalence of glutamate receptor subunit 2 (GluR2)-lacking alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptors is a hallmark of excitotoxicity-related neurodegenerative diseases. Topiramate (TPM) is a structurally novel anticonvulsant with a well-known modulatory effects on AMPA/kainate subtypes of glutamate receptors. The present study aimed at investigating the neuroprotective potential of TPM on 3-nitropropionic acid (3-NP)-induced striatal neurodegeneration and Huntington's disease-like symptoms. Rats were injected with 3-NP (10 mg/kg/i.p.) for 14 days. TPM (50 mg/kg/p.o.) was given once a day, 1 h before 3-NP. TPM amended 3-NP induced changes in neurobehavioral performance, striatal neurotransmitters levels and histopathological injury. 3-NP control rats showed a significant ablation in the mRNA expression of Ca 2+ -impermeable Glu2R subunit along with an elevation in its regulatory protein (protein interacting with C kinase-1) PICK1, an effect that was largely reversed by TPM. TPM in addition, enhanced the phosphorylation of the protein kinase B/glycogen synthase kinase-3β/cAMP response element binding protein (Akt/GSK-3β/CREB) cue. Moreover, improvement in oxidative status, suppression of caspase-3 activity and restoration of striatal BDNF were noticed following treatment with TPM. The current study revealed that TPM boosted the neuroprotective (Akt/GSK-3β/CREB) pathway by its negative modulatory effect on AMPA glutamate receptors as well as its direct antioxidant property. Highlights: GluR2-lacking AMPA receptors accelerated the excitotoxicity instigated in HD. Topiramate mitigated 3-NP induced motor impairment and striatal neurotoxicity. Topiramate modulated AMPA receptors and activated Akt/GSK-3β/CREB signaling pathway. Topiramate offers a feasible therapeutic tool decelerating the progression of HD.